Implementasi Hukum Terhadap Tindak Pidana Ilegal Loging Di Kawasan Hutan Diklat Sisimeni Sanam - Agusthinus Banik; Jimmy Pello; Aksi Sinurat (Law Faculty, Nusa Cendana University, 2026)
jungle are a gift from God Almighty that must be appreciated by the Indonesian people. Sisimeni Sanam Training Forest is a forest area designated as a means and infrastructure for practice in supporting forestry training activities and as a natural laboratory for developing science and technology (Iptek) in the forestry sector. Various problems that occur must be handled properly, one of which is the case of illegal logging that often occurs. Therefore, the author is interested in researching cases of illegal logging that occur in the Sisimeni Sanam Training Forest. The formulation of the problem in this study is: (1). How is the application of law to cases of illegal logging crimes committed in the Sisimeni Sanam Training Forest area? (2). What are the obstacles faced by officers in handling illegal logging in the Sisimeni Sanam Training Forest area? This study uses an empirical legal research method, which was conducted at the Sisimeni Sanam KHDTK. This study uses an interview guide for two informants. Data are presented and analyzed in a qualitative descriptive manner. application of law by officers in providing a deterrent effect to perpetrators is quite effective in preventing similar actions from happening again. (2). Obstacles for officers in dealing with illegal logging, the obstacles faced by officers in dealing with illegal logging are caused by several factors, such as lack of transportation and the vast area of ​​forest in the Sisimeni Sanam Training Forest, which is one of the obstacles for officers.